Clinical Characteristics and Outcomes of Adults with Nephrotic Syndrome Due to Minimal Change Disease - Sophia Lionaki (Journal of Clinical Medicine, 2021)
Purpose: Minimal change disease (MCD) is considered a relatively benign glomerulopathy, as it rarely progresses to end-stage kidney disease. The aim of this study was to describe the characteristics and outcomes of adults with MCD and identify potential risk factors for relapse. Patients & Methods: We retrospectively studied a cohort of adults with biopsy-proven MCD in terms of clinical features and treatment outcomes. Baseline characteristics and outcomes were recorded and predictors of relapse were analyzed using logistic regression multivariate analysis. Results: 59 patients with adult-onset primary MCD with nephrotic syndrome were included. Mean serum creatinine at diagnosis was 0.8 mg/dL (±2.5) and estimated GFR (eGFR) was 87 mL/min/1.73 m2 (±29.5). Mean serum albumin was 2.5 g/dL (±0.8) and 24 h proteinuria 6.8 g (±3.7). Microscopic hematuria was detected in 35 (58.5%) patients. 42 patients received prednisone alone, six patients received prednisone plus cyclophosphamide, five patients received prednisone plus cyclosporine, one patient received prednisone plus rituximab and five patients did not receive immunosuppression at all since they achieved spontaneous remission. During a mean follow up time of 34.7(22.1) months, 46.1% of patients experienced at least one episode of relapse. The mean age of patients who did not experience a relapse was significantly higher than that of patients who relapsed while relapsers had a significantly longer duration of 24 h proteinuria prior to biopsy compared to non-relapsers. Overall, 10% of patients experienced acute kidney injury while the mean eGFR at the end was 82 mL/min/1.73 m2 (±29.1) and one patient ended up in chronic dialysis. Overall, the proportion of non-relapsers, who experienced acute kidney injury (17%) was significantly higher than the one recorded among relapsers (0%).Conclusion: In this series of patients, almost 46% of adult-onset nephrotic MCD patients experienced a relapse, although their renal progression was rare. Younger onset age was an independent risk factor for relapse in adult-onset MCD patients.